2009
DOI: 10.1107/s0907444908041814
|View full text |Cite
|
Sign up to set email alerts
|

De novosulfur SAD phasing of the lysosomal 66.3 kDa protein from mouse

Abstract: The 66.3 kDa protein from mouse is a soluble protein of the lysosomal matrix. It is synthesized as a glycosylated 75 kDa preproprotein which is further processed into 28 and 40 kDa fragments. Despite bioinformatics approaches and molecular characterization of the 66.3 kDa protein, the mode of its maturation as well as its physiological function remained unknown. Therefore, it was decided to tackle this question by means of X-ray crystallography. After expression in a human fibrosarcoma cell line, the C-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…ratio for data set B was only 1.11, which is significantly below the empirically estimated threshold of 1.5 for successful S-SAD (Weiss et al, 2001;Mueller-Dieckmann et al, 2005). As previously noted by others (Sarma & Karplus, 2006;Lakomek et al, 2009), the R anom /R p.i.m. threshold may be adjusted to a lower limit, i.e.…”
Section: In-house S-sad Phasingmentioning
confidence: 48%
See 1 more Smart Citation
“…ratio for data set B was only 1.11, which is significantly below the empirically estimated threshold of 1.5 for successful S-SAD (Weiss et al, 2001;Mueller-Dieckmann et al, 2005). As previously noted by others (Sarma & Karplus, 2006;Lakomek et al, 2009), the R anom /R p.i.m. threshold may be adjusted to a lower limit, i.e.…”
Section: In-house S-sad Phasingmentioning
confidence: 48%
“…threshold may be adjusted to a lower limit, i.e. 1.1, as found in the present study and as indicated previously in the S-SAD solution of the lysosomal mouse protein (Lakomek et al, 2009). Similarly, the SigAno parameter, or |Á ano |/(Á ano ), may also require adjustment.…”
Section: In-house S-sad Phasingmentioning
confidence: 66%
“…improved detectors, phasing with the weak anomalous signal from intrinsic scatterers has become a possible option, although high-quality data are required. These are more readily obtained when high symmetry enables a high data redundancy to be achieved, but low-symmetry examples have also proved successful (Lakomek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Two important factors contributed to the success of the lysozyme and obelin cases: (i) the development of the iterative single-wavelength anomalous scattering (ISAS) method coupled with solvent flattening (Wang, 1985) and (ii) advances in instrumentation and data-processing software which ensured the collection and processing of much more accurate anomalous diffraction data. Since then, many more de novo crystal structures have been solved using synchrotron X-rays (Gordon et al, 2001;Ramagopal et al, 2003;Brown et al, 2002;Weiss et al, 2004;Li et al, 2002;Madauss et al, 2004;Agarwal et al, 2006;Wagner et al, 2006;Lakomek et al, 2009;Goulet et al, 2010) or in-house Cu or Cr X-rays (Yang & Pflugrath, 2001;Debreczeni, Bunkó czi, Girmann et al, 2003;Debreczeni, Bunkó czi, Ma et al, 2003;Yang et al, 2003;Kitago et al, 2005;Nagem et al, 2005;Watanabe et al, 2005;Ren et al, 2005;Sarma & Karplus, 2006;Nan et al, 2009;Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among the variables associated with data-collection strategies research papers involving longer wavelengths (Cianci et al, 2008;Ramagopal et al, 2003), the choice of the wavelength is one of the most important factors. To date, wavelengths for successful cases of de novo S-SAD phasing have mostly been within the range 1.54-2.50 Å (Lakomek et al, 2009;Weiss et al, 2001). The relationship between S-SAD signal and data quality using Xrays of wavelength beyond 2.5 Å has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%